Bermuda : Assessment of the Supervision and Regulation of the Financial Sector. (IMF Staff Country Reports; Country Report ;, 2008)
This paper presents an assessment of Financial Sector Supervision and Regulation for Bermuda. The Bermudian authorities have made impressive progress in developing and implementing a risk-focused approach to supervision across the range of their sectoral supervisory responsibilities. Full rollout of the risk-based regulatory system to all market segments is, however, required for achievement of comprehensive oversight of the market. To support the introduction of a formal risk-based supervisory system, the banking department has been restructured.